PENINGKATAN PEMAHAMAN JARINGAN DAN KOMUNIKASI DATA SISWA SMK N 1 BANYUMAS MELALUI PELATIHAN BERBASIS SIMULASI CISCO PACKET TRACER - Bhakti Sihanjono; Aditya Tri Prabowo; Faiq Irfandi Salim; Rasya Nizar Pradipa (CV. Denasya Smart Publisher, 2026)
The rapid development of computer networks has increased the demand for vocational students to master not only theoretical concepts but also practical networking skills. However, many vocational high school students still experience difficulties in applying networking concepts in real or simulated environments. This community service activity aimed to improve students’ understanding and technical skills in computer networking and data communication through simulation-based training using Cisco Packet Tracer. The activity was conducted at SMK Negeri 01 Banyumas and involved students of grade XI majoring in Computer and Network Engineering. The method used consisted of initial observation, preparation of training materials, delivery of theoretical concepts, hands-on simulation practice, and evaluation of participants’ responses. The results showed an improvement in students’ ability to configure basic network devices, understand IP addressing and subnetting, and analyze data communication processes through simulation. In addition, students demonstrated increased awareness of network security and digital ethics. This activity indicates that simulation-based training is an effective approach to strengthen vocational students’ competencies in computer networking and data communication.